Desenvolvimento de cerâmicas de nitreto de boro hexagonal por sinterização por spark plasma e prensagem a quente (uniaxial e isostática) - Almeida, Tatiani Falvo (2019)
This research has uniquely investigated the influence of three pressure sintering processes and the effect of adding calcium oxide – CaO, in microstructure, density and electrical resistivity of hexagonal boron nitride (h-BN). It was necessary a systematic study to analyze not only the influence of CaO, but also the effect of the type of sintering technique on these properties. The study has used two highly pure commercial h-BN powders (PSHP325 and PCPS302), which have different physical and chemical characteristics, particularly in terms of particles morphology and size, and the additive CaO in concentrations of 2.5%, 5% and 10% in weight. Mixing and homogenization of h-BN and CaO powders were made mechanically, in alcohol medium, followed by drying process. Sintering the nitride with and without the addition of CaO was made by hot pressing (HP), hot isostatic pressing (HIP) and spark plasma sintering (SPS), using different processing conditions, changing temperature, pressure and sintering stage. In terms of pure nitride, samples sintered by HIP, using raw material with higher medium particle size – D50 around 11 μm (PSHP325), presented aleatory grain orientation in the microstructure and the highest apparent density (DA) and dielectric constant – 2.08 g/cm3 and 5.75, respectively, when compared to the samples sintered by the other techniques. Related to the effect of CaO addition, the best results of DA were obtained to the mixtures containing 5% weight of the additive, independently of the sintering technique used. However, the sample resultant of the SPS processing, using finer h-BN powder (PCPS302) – D50 around 2 μm, was the one with higher density between all the analyzed samples, corresponding to 94.4% DT of the mixture, associated to a microstructure of aligned grains perpendicularly to pressing direction and a dielectric constant of 4.7.